Analisis Putusan Hakim Pengadilan Negeri Kuala Simpang Nomor 202/Pid.Sus/2015/PN Ksp Dikaitkan Pasal 80 Ayat (3) jo. Ayat (4) UU Perlindungan Anak: Analisis Putusan Hakim Pengadilan Negeri Kuala Simpang Nomor 202/Pid.Sus/2015/PN Ksp Dikaitkan Pasal 80 Ayat (3) jo. Ayat (4) UU Perlindungan Anak - Pardede, Sarah Berliana; Astuti, Pudji (NOVUM : JURNAL HUKUM, 2018)
Article 44 paragraph (2) of the PKDRT Law regulates the threat of punishment for acts of physical violence within the scope of the household which result in serious injury, where the category of serious injuries refers to Article 90 of the Criminal Code, including the pregnancy loss. The purpose of this research is to analyze and find out whether a pregnancy loss due to domestic violence can be equated with a serious injury as regulated in Article 90 of the Criminal Code, and whether Article 44 of the PKDRT Law on physical violence in the household sphere is in accordance with Article 80 of the Child Protection Law. This research is a normative legal research using a statutory approach, a conceptual approach, and a case approach. The legal materials used are primary and secondary. The analysis technique uses a prescriptive method. The results of this study indicate that the incidence of the abortion of a woman's womb and bleeding experienced by pregnant women due to domestic violence in Kuala Simpang District Court Decision No. 202 / Pid.sus / 2015 / PN.KSP can be equated with Serious Injury Article 90 of the Criminal Code. A child in the womb who dies cannot necessarily be equated with serious injuries in Article 90 of the Criminal Code. Then, Article 44 of the PKDRT Law is not in accordance with Article 80 of the Child Protection Law. The actions of the perpetrator (SM) include an concursus idealist.